1993
DOI: 10.1016/s0022-5347(17)35405-8
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Prostatism: A Population-Based Survey of Urinary Symptoms

Abstract: To establish the age-specific prevalence of urinary symptoms among a community-based cohort of men, a randomly selected sample of men were screened and invited to participate in a longitudinal survey of urinary symptoms. The population of Olmsted County, Minnesota, as enumerated by the Rochester Epidemiology Project, formed the sampling base for this study. Men between 40 and 79 years old with no history of prostate or other urological surgery, and who also were free of conditions associated with neurogenic bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
329
2
14

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 676 publications
(366 citation statements)
references
References 17 publications
16
329
2
14
Order By: Relevance
“…However, only 10 % of men with such symptoms are treated with prescription medications. 14,15 As BPH is underdiagnosed and undertreated, the potential exists for large market expansion through DTCA. 15 Medical therapy for BPH includes alpha 1-adrenergic antagonists (alphablockers), 5-alpha reductase inhibitors (5ARIs), or both in combination.…”
Section: Study Drugsmentioning
confidence: 99%
“…However, only 10 % of men with such symptoms are treated with prescription medications. 14,15 As BPH is underdiagnosed and undertreated, the potential exists for large market expansion through DTCA. 15 Medical therapy for BPH includes alpha 1-adrenergic antagonists (alphablockers), 5-alpha reductase inhibitors (5ARIs), or both in combination.…”
Section: Study Drugsmentioning
confidence: 99%
“…1 Community-based studies have evaluated the prevalence of symptomatic BPH or lower urinary tract symptoms (LUTS) by age in several European countries, 2 ± 5 the US 6 and Japan. 7 Results show that one in four men aged 50 y have LUTS, increasing to one in two men aged 65 y.…”
Section: Prevalence Of Bphmentioning
confidence: 99%
“…4 These findings were also seen in the Olmsted County Study, in which randomly selected males aged 40-79 years found moderate to severe LUTS increased with age from 26% in men 40-49 years old to 46% in men 70-79 years old. 5 ED, or the inability to obtain and/or maintain an erection suitable for sexual intercourse, also increases in prevalence as men age. The Massachusetts Male Aging Study showed that 52% of men between 40 and 70 years of age experienced some level of ED, from 39% in men in their 40s to 67% in men in their 70s.…”
Section: Introductionmentioning
confidence: 99%